Student Satisfaction as Mediation Variabel of Brand Image and Service Quality Influence on Student Loyalty - Murtiningsih, Dewi; Usino, Wendi; Elizabeth, Elizabeth; Juariyah, Lohana (Ekonomi Bisnis, 2021)
This research aims to find out student satisfaction as a mediation variable of brand image and service quality influence on student loyalty. This research is explanatory. The total sample used in this research is 110 students. The questionnaire is used as an instrument to collect the respondent's data, which will be tested using validity and reliability test. The analysis instrument used in this research is Smart PLS. The research results show that brand image does not influence student satisfaction, the brand image does not influence student loyalty,  student satisfaction does not mediate the influence of brand image on student loyalty, student satisfaction influences student loyalty, service quality influences student satisfaction, service quality does not influence student loyalty, and student satisfaction mediates the influence of service quality on student loyalty. It seems that in private university in medium rank, brand image of university does not influence student satisfaction and student loyalty. Therefore, for next research, it is better to consider the rank of university and its status as private or state university and also age of university. Furthermore, the instrument should be specific for higher education context.Keywords: Brand Image; Service Quality; Student Satisfaction; Student Loyalty